Pharmacokinetics/pharmacodynamics of glucocorticoids: modeling the glucocorticoid receptor dynamics and dose/response of commonly prescribed glucocorticoids - David Levitt (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: The main features of the dynamics of the glucocorticoid receptor (GR) have been known for 50 years: 1) in the absence of glucocorticoid (G), the receptor is localized entirely in the cytoplasm; 2) upon G binding, GR is converted into a tightly bound G form and is rapidly imported into the nucleus where it can bind DNA and modulate transcription; 3) nuclear export of GR is very slow; and 4) the nuclear form of GR can recycle through an unbound form, back to the bound transcription modulating form without leaving the nucleus. Experimental approach: A kinetic model that captures these features is presented, a set of model parameters for dexamethasone is derived, and the clinical implication for the commonly used glucocorticoids is discussed. Key results: At the high concentrations normally used to describe G pharmacodynamics, the model reduces to the standard Michaelis-Menten equation with a Km that is a function of 4 model parameters. At very low concentrations, it reduces to another Michaelis-Menten equation with about a 1000-fold greater affinity, eg. at the nadir human endogenous cortisol concentration, the full model GR activity is 2.6 times greater than that predicted by extrapolation of the high concentration results. Conclusion: The model is used to relate normal human 24-hour endogenous plasma cortisol levels to transcriptional activity and is applied to the commonly prescribed glucocorticoids (dexamethasone, methylprednisolone, prednisone) in an attempt to provide a pharmacological rationale for the very large therapeutic dosage range that has been traditionally used.